New ways of working; delivering better care for people with long-term conditions*. Issue 5 (3rd September 2017) - Tzortziou Brown, Victoria; Patel, Irem; Thomas, Nicola; Tomlinson, James; Roberts, Rachel; Rayner, Hugh; Ashman, Neil; Hull, Sally
Abstract: Background : The cost-effectiveness of the traditional outpatient model for specialist care provision is increasingly being questioned in view of the changing patient needs, workforce challenges and technological advances. Setting : This report summarises two RCGP London events showcasing new ways of delivering care for long-term conditions. Questions : What are the alternative approaches to the traditional outpatient model and do they have common themes? What are the challenges and opportunities of these new models of care? Methods : Presentation of examples of new ways of long-term condition care delivery and round-table facilitative discussion and reflection on the challenges and solutions around service re-design and implementation, the commissioning and funding of new models of care, the facilitation of system-wide learning and the collection of data for evaluation. Results : Different ways of delivering care for people with Chronic Kidney Disease (CKD) and Chronic Obstructive Pulmonary Disease (COPD) were presented. Most of the interventions included virtual clinics (during which patient care was reviewed by a specialist remotely without the need for a face-to-face consultation), improved communication between primary and secondary care clinicians, an element of referral triage/prioritisation, the use of trigger tools to identify people at risk of deterioration, patient education and a multi-disciplinary approach. Discussion-conclusions : Different models to the traditional outpatient long-term condition care are feasible and can result in improvements in the quality of care and staff satisfaction. However, such initiatives require careful planning, close collaboration between health care professionals and allocation of appropriate resources and training within primary care. There is also a need for systematic evaluation of such pilots to assess their cost-effectiveness and their acceptability to clinicians and patients. This requires systematic collection of population level data, agreement on the key outcomes for evaluation and a commitment of all stakeholders to sharing learning and resources to enable continuous improvement.